Management of Local Biological Resources for Islamic Boarding School Food Security: A Study of Santri Perceptions and Actions Based on Islamic Values - Hidayatullah Hidayatullah; Eko Budi Minarno (Community: Jurnal Hasil Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to analyze the perceptions and actions of Islamic boarding school students (santri) toward food security based on biological resources and Islamic teachings at Al-Istiqomah Islamic Boarding School in Diwek District and Urwatul Wusqo Islamic Boarding School in Peterongan District, Jombang Regency. The study employed a descriptive qualitative approach through observation, interviews, and documentation involving students, administrators, and caretakers of the boarding schools. The results show that both Islamic boarding schools have implemented food security programs through agricultural and fishery cultivation as a form of food self-sufficiency. The biological resources developed include rice, corn, vegetables, and the cultivation of catfish, tilapia, and pangasius fish. The food security programs are supported by the availability of land, water resources, favorable environmental conditions, and the active participation of the students. The students’ perceptions of food security tend to be positive, as it is viewed as an implementation of Islamic teachings concerning environmental stewardship, self-reliance, and the prohibition of excessive behavior. The students’ actions are demonstrated through their direct involvement in seedling preparation, planting, maintenance, and the utilization of harvest products. This study indicates that Islamic boarding schools have strategic potential as centers for food security education based on Islamic values and sustainable biological resources.